Introduction of innovative methods to solve the problem of deviant behavior (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the study of deviant behaviour duringadolescence (the theoretical aspect) and the description of the possibilitiesfor resolving this problem with the help of innovative methods. A briefoverview of the sources about the causes, the types of deviant behaviour as astable behaviour of the individual, that deviates from the generally accepted,prevalent, stable social norms, is given. The results of an integrated studyof deviant adolescents (the involvement of experts, monitoring, diagnosis)are represented. Innovative forms of work about the prevention of deviantbehaviour and its correction: the creation of a bank of convincing evidencein terms of behavioural disorders, «publicity of the act», reinforcement, —are represented
Keywords: deviant behaviour, innovative forms, prevention, adjustment (correction), integrated study